2014
DOI: 10.1111/cei.12349
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific over-expression of human cartilage glycoprotein 39 on CD4+CD25+ forkhead box protein 3+ regulatory T cells in the generation of glucose-6-phosphate isomerase-induced arthritis

Abstract: SummaryHuman cartilage gp-39 (HC gp-39) is a well-known autoantigen in rheumatoid arthritis (RA). However, the exact localization, fluctuation and function of HC gp-39 in RA are unknown. Therefore, using a glucose-6-phosphate isomerase (GPI)-induced model of arthritis, we investigated these aspects of HC gp-39 in arthritis. The rise in serum HC gp-39 levels was detected on the early phase of GPI-induced arthritis (day 7) and the HC gp-39 mRNA was increased significantly on splenic CD4 cells, T cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Also, peripheral blood derived CD16 positive mononuclear cells with a macrophage phenotype infiltrating into the synovium are another potential cellular source of YKL-40 in RA [ 15 ]. In addition, lymphocytes may produce YKL-40: Recent study by Tanaka et al using glucose-6-phospatase isomerase immunized mice as a model of RA, showed overexpression of YKL-40 in splenic regulatory T cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, peripheral blood derived CD16 positive mononuclear cells with a macrophage phenotype infiltrating into the synovium are another potential cellular source of YKL-40 in RA [ 15 ]. In addition, lymphocytes may produce YKL-40: Recent study by Tanaka et al using glucose-6-phospatase isomerase immunized mice as a model of RA, showed overexpression of YKL-40 in splenic regulatory T cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within RA joints, YKL-40 has been recognized as a major secretory protein of articular chondrocytes [ 14 ]. Synovial cells, macrophages and neutrophils infiltrating into the RA synovium also produce YKL-40 [ 1 , 14 – 16 ], and just recently, splenic T-cells have been added to the list of YKL-40 producing cells in RA [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It suggested that HC gp-39 in CD4 + T cells might play a regulatory role in RA [ 81 ]. Studies of the presentation of immunodominant epitope of HC gp-39 by shared epitope-positive synovial dendritic cells indicated that this presentation was associated with characteristic histologic features of follicular synovitis and is highly specific for RA [ 82 ]. Autoantibodies against HC gp-39 were detected only in the sera of 8% of RA patients, but not in samples from SLE patients or healthy donors [ 83 ].…”
Section: Chondrocyte Antigens As Potential Targets In Inflammatory Jomentioning
confidence: 99%
“…It was also found that chronic arthritis spontaneously developed by the K/BxN T cell receptor-transgenic mouse, with many features of human rheumatoid arthritis disease, is initiated by T cell recognition of GPI enzyme [9]. Moreover, immunization with human recombinant GPI protein induced arthritis in several mice models [10][11][12]. Recent literature also suggests a positive correlation between anti-GPI autoantibody and the arthritis disease in humans [13].…”
Section: Introductionmentioning
confidence: 98%